A "nova cultura da adoção": reflexões acerca do cenário atual da adoção no Brasil - Souza, Maria de Lourdes Nobre (2016)
This research aims to describe and analyze the argument sustained by professionals from different sectors of society related to adoption that support the "new culture of adoption". This refers to a set of ideas that have been introduced in Brazil for almost three decades by the adopting national movement, which currently enjoys a great political insertion in state spheres. The "new culture of adoption" objectives guarantee the right to family living and community to institutionalized children and adolescents by encouraging the practice of adoption. It is observed a certain stuck to their roots disregard towards generating factors that lead children and adolescents not to stay in their families of origin, need to be placed in a foster family. Therefore, it is the question if the current disseminators discourses of "new culture of adoption" would not be extolling the adoption as a "solution" more feasible for the problems of the needy children in the country and with it, covering up and naturalizing the social issues that lead many socially excluded families to lose their parental authority over their children. The survey was conducted from the content analysis of seven lectures given by professionals in defense of the "new culture of adoption", which were part of the program of the First online National Congress on Adoption (CONADOTE), occurred in 2015. Five categories emerged from the analysis of these lectures: the situation of institutionalized children and adolescents, examination of legislation and legal adoption procedures, references to the service network, the disqualification of the biological family and the adoption as a solution, which were analyzed based the theoretical framework of Social Psychology in a socio-historical perspective, and related areas. It is concluded that the "new culture of adoption", despite victories in relation to the increased visibility of the practice of adoption, remains fighting for the same ideals of the beginning of its creation, seeking to ensure family and community life to such public children and youth by finding families willing to adopt it, confirming the idea of adoption as a solution to the problems that quota had as "no family". Thus, there is a disqualification of the origin family and the fight for the adoption ceases to be an exceptional measure, as it is considered legal. Finally, it appears that the ideas defended by the "new culture of adoption" are inscribed within the larger interests of the current economic order, characterized by the ideals of neo-liberal capitalism.